Cabin and orchards in the Santa Cruz Mountains - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Landscape view of cabin and orchards in the Santa Cruz Mountains. The exact location for this image is unknown. The speckling on far left side of the image is due to nitrate degradation in the original film.